Where the dead wait [large type] - Wilkes, Ally (Center Point Large Print, 2024)
"William Day should be an acclaimed Arctic explorer. But after a failed expedition, in which his remaining men only survived by eating their dead comrades, he returned in disgrace. Thirteen years later, his second-in-command, Jesse Stevens, has gone missing in the same frozen waters. Perhaps this is Day's chance to restore his tarnished reputation by bringing Stevens -- the man who's haunted his whole life -- back home. But when the rescue mission becomes an uncanny journey into his past, Day must face up to the things he's done. Abandonment. Betrayal. Cannibalism. Aboard ship, Day must also contend with unwanted passengers: a reporter obsessively digging up the truth about the first expedition, as well as Stevens's wife, a spirit-medium whose séances both fascinate and frighten. Following a trail of cryptic messages, gaunt bodies, and old bones, their search becomes more and more unnerving, as it becomes clear that the restless dead are never far behind. Something is coming through."--